Oropharyngeal dysbiosis affects postoperative tissue reparative capacity in patients with congenital disorders of maxillofacial region - Zaira F. Kharaeva; Vladimir A. Vissarionov; Sofyat M. Mustafaeva; Melena M. Yusupova; Alina R. Shogenova; Dzhamilya. Sarakaeva; Diana V. Degoeva; Vladimir V. Smeianov (Russian Open Medical Journal)
Background — One of the main causes of hyperergic postoperative tissue response could be a prolonged opening in the septum between normally isolated anatomical regions, e.g., of the nasal cavity and oropharynx in patients with congenital disorders of maxillofacial region, which leads to anomalous exchange of their microbiotas. Objective — The objective of this study was to determine the composition of culturable facultative anaerobic microbiota of oronasopharyngeal mucosa, and to identify cytokine profiles in patients with congenital disorders of maxillofacial region in both preoperative and postoperative periods. Methods and Results — Our study is based on the results of examining the children with unilateral congenital cleft of upper lip (CL) before and after surgery, as well as examining the children with simultaneous unilateral congenital cleft of upper lip and palate (CLP) before and after primary rhinocheiloplasty. We used ELISA to determine the content of interleukin-10 (IL-1β) and interleukin-10 (IL-10) in the samples of blood serum and mucosal surfaces. The study of culturable microflora was conducted in patients before the surgery and during a postoperative period, specifically at one, three, six, and twelve months. Isolation of pure bacterial cultures was performed via conventional bacteriological methods followed by identification using MALDI-TOF testing. Before the surgery, microbial colonization was observed at significantly higher levels in CLP children than in healthy children. After the surgery, microbiological indicators partially came to normal values solely in CL patients. Local IL-1β concentrations remained significantly higher than those found in healthy subjects. In terms of postoperative dynamics, blood plasma antioxidant activity declined below normal values in CLP patients. Conclusion — Our study demonstrated the need for preoperative eradication of potential pathogens (e.g., Staphylococcus aureus, Klebsiella spp., Candida spp. and Streptococcus spp.), preferably, via using non-antibiotic approaches, such as probiotics and phage therapy, as well as supportive integrative therapy (e.g., using antioxidants).